Improving Radiance simulation workflow with process of anti-aliasing and tone-mapping to enhance users’ experience in VR environments - Monteoliva, Juan Manuel (2023)
Recently, the use of VR is developing and spreading to be used for different applications: among them the evaluation of luminous environments and their characteristics by potential occupants for visual comfort assessment. Here, an improved simulation workflow based on Radiance use is presented to enhance the visualization quality in lower resolution VR HMDs devices and consequently users’ immersion experience. The method is based on the use of equirectangular projection, digital signal anti-aliasing processing and tone-mapping trough ‘normtiff’ Radiance command. Results demonstrate that the method increases the photo- realism of the model, improving users’ experience.